La vida social de los precios: evaluaciones monetarias y acción económica en los mercados de la seguridad privada = The social life of prices: monetary assessments and economic action in private security markets - Valcarce, Federico Lorenc (Civitas - Revista de Ciências Sociais)
Based on a study of private security markets in Argentina, this paper discusses the way in which prices are produced, perceived, interpreted and manipulated in the course of economic actions of various actors. My work is based on thirty interviews with leaders of security companies and forty interviews with different kinds of customers of these companies, as well as observations made in twenty companies in the sector and informal exchanges with key informants. In addition, I use materials produced by public institutions, chambers and professional organizations in the field of security, and by the companies themselves. In this paper, I show that prices are negotiated in the course of market transactions and that the actors introduce principles of interaction other than competition